Conduct Problems in Children Attending Pre-Primary Schools in Rural Areas of Pakistan (Journal of Education and Educational Development, 2020)
The aim of this study was to explore the conduct problems faced by school going children in the rural areas of Pakistan. Two hypotheses were formulated to explore the significant differences between the intervention and non-intervention groups and gender on the variables of conduct and internalization. The data of a total 386 young children were collected from three different regions, who were enrolled in government pre-primary classes. The children under study comprised two kinds of schools: intervention schools that had early childhood interventions, and non-intervention schools. The data analysis revealed no significant difference between children in intervention and non-intervention schools. However, there was a gender difference found in the variables of conduct and internalization. The conclusion of the study was framed to provide implications of the study for professionals.